Ethanolic extract of Kaempferia parviflora interrupts the mechanisms-associated rheumatoid arthritis in SW982 culture model via p38/STAT1 and STAT3 pathways - Patiwat Kongdang (2019)
© 2018 Elsevier GmbH Background: Kaempferia parviflora Wall. ex Baker (KP) has long been used in traditional medicine to treat various diseases because active compounds in rhizome extracts are important anti-inflammatory agents. Purpose: This study aims to investigate the effects of an ethanolic extract of KP on the molecular mechanisms associated with rheumatoid arthritis (RA), which was induced by a combination of proinflammatory cytokines (IL-1β or TNF-α with IL-17A) in a human synovial sarcoma cell line (SW982) culture model. Methods: SW982 cells pretreated with cytokines were incubated with KP extract at 3–30 µg/ml, or three major compounds of KP (5,7-dimethoxyflavone, 5,7,4′-trimethoxyflavone, and 3,5,7,3′,4′-pentamethoxyflavone) for up to 72 h. Dexamethasone was used as positive control. RA-associated genes and inflammatory products were measured in parallel with cell death genes. Apoptosis by flow cytometry and migration assay were also analyzed. Western blotting was used to examine the effects on intracellular signaling mechanisms. Results: KP extract markedly reduced the expression of genes and levels of proinflammatory cytokines, inflammatory mediators, and matrix-degraded enzymes, but neither induced apoptosis nor altered the cell cycle. Its major constituents differently exerted suppressive effects on inflammatory genes. The KP extract downregulated the expression of genes associated with autophagosome and necroptosome formations. The extract also inhibited cell migration, reduced the mRNA expression of cadherin-11, and selectively reduced the phosphorylation of p38 MAPK, STAT1, and STAT3 signaling molecules, but did not interfere with the NF-κB pathway. Conclusion: These results suggest that the anti-arthritic potential of KP extract results from anti-inflammation and anti-migration via the suppression of the cytokines-induced p38/STAT1 and STAT3 pathways.